The Comparative Efficacy of Conventional and Crown-Down Root Canal Preparation Techniques in Relation to the Extrusion of Apical Debris - Arifian, Rahmat; Anang Kusbianto (Phlox Institute: Indonesian Medical Research Organization, 2023)
Numerous scientific investigations have been undertaken to assess the efficacy of standard root canal preparation methods and the crown-down procedure in mitigating the ejection of apical debris. The aforementioned research examines multiple facets, encompassing the efficacy of canal cleaning, the potential for debris extrusion, and their influence on the outcome of root canal therapy. The objective of this study is to evaluate the efficacy of conventional and crown-down root canal preparation methods in relation to the extrusion of apical debris. The literature search used a lot of different databases, like PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar, to look into how well traditional and crown-down root canal preparation methods work for getting debris out of the root canal. Traditional methods of root canal preparation have been extensively employed in the field of endodontics. While root canal cleaning and shaping techniques have demonstrated efficacy, there is still a potential danger of apical debris extrusion. Several factors contribute to the level of risk involved in dental procedures. These factors encompass the use of instruments, the amount of pressure applied during preparation, the effectiveness of irrigation, and the level of experience possessed by the dentist. In conclusion, the efficacy of both methodologies is contingent upon various aspects, including the level of expertise possessed by the dentist, the specific instruments employed, the irrigation technique employed, and the thoroughness of the case examination. The particulars of each case and the dentist's personal preference should guide the choice of either procedure.